Evaluating Stars Temperature Through the B-V Index Using a Virtual Real Experiment from Distance: A Case Scenario for Secondary Education. - Dintsios, Nikolaos; Artemi, Stamatia; Polatoglou, Hariton (International Journal of Online and Biomedical Engineering (iJOE), 2018)
In this paper we propose a scenario for secondary education at which students could estimate the temperature, the radius and the age of stars. To achieve this, we built a virtual real experiment which can be performed from distance on any portable device. Students can connect to a webpage and choose a star from a list. After applying B and V filters they obtain the B and V magnitude. Consequently, they calculate the B-V index of a star and using a simple formula they estimate the star’s surface temperature. Furthermore, guided through a worksheet and with the use of Hertzsprung–Russell diagram they can estimate the radius and the age of the star.